INDENTIFIKASI PELUANG DAN TANTANGAN PENANGGULAGAN STUNTING DI DESA PASSO KECAMATAN BAGUALA KOTA AMBON - Leo Siregar; Inta P. N. Damanik; J. M. Luhukay (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
Stunting is a condition of impaired child growth, characterized by an abnormal height for their age. This is generally caused by chronic malnutrition and repeated infections during the early period of life, especially in the first 1,000 days. This condition not only affects the physical but also the development of children's thinking and learning abilities which have the potential to affect their learning and productive capacity later. Stunting can also be defined as a condition where toddlers experience obstacles in physical growth due to long-term malnutrition, which results in children being shorter than children of the same age. Stunting is the development of the brain and intelligence of children. Apart from malnutrition, environmental factors and unhealthy food and lack of attention or family support for children's health are the causes of stunting. Stunting can be anticipated if a healthy environment and parental attention to the growth and development of children's activities are always maintained. Becoming one of the factors in overcoming stunting.